Pro-poor public investment program - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
As policymakers decide how to allocate public spending to achieve higher growth and poverty reduction, they need a clear understanding of how public investments translate into development outcomes. In many cases policymakers also need better information about how to improve the performance of the institutions that implement public investments. To help meet these information requirements, IFPRI’s Pro-Poor Public Investment Program works with governments as well as with the private sector, civil society, and international organizations to carry out research on the role of public investment and on strategies that can better connect public investments and policies with development goals. The program comprises policy-oriented research, capacity building, and policy communication.